Volunteering in Israel – mobilized culture or norm - Shamir-Tixell, Edith (Humaniora. Czasopismo Internetowe, 2019)
The purpose of this paper is to present Israel volunteering norm and Israelis’ attitude toward volunteering. Data shows that the rate of volunteering in Israel is declining and that Israelis attitude towards volunteering has changed. A committee on volunteering within the framework of the Interdisciplinary Round Table in the Prime Minister’s Office was established to promote volunteering and social participation in Israel. There is a high-school program, to promote volunteering among teenagers that everyone must go through for 3 years. Much effort is dedicated to increasing motivation for volunteering, However, the volunteer percentage among adults are not rising. A Situational description.